Web reasoning and rule systems : 10th International Conference, RR 2016, Aberdeen, UK, September 9-11, 2016, Proceedings /: 10th International Conference, RR 2016, Aberdeen, UK, September 9-11, 2016, Proceedings. (2016) - Unknown
No abstract available